2013
DOI: 10.17221/663/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Foliar fertilization with molybdenum in sunflower (Helianthus annuus L.)

Abstract: The objective of the vegetation experiment established in [2008][2009][2010][2011] was to explore the effect of the time and dose of foliar molybdenum (Mo) application on the yield and quality of sunflower. Four treatments were established in the experiment: (1) control -not fertilised with Mo; (2) application of 125 g Mo/ha in the growing stage of 4 developed leaves (V-4); (3) application of 125 g Mo/ha at the beginning of elongation growth (R-1), and (4) split rate of Mo application of 62 g Mo/ha at stage V-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although, we did not quantify the amount of solar radiation intercepted by the test varieties in this study, Dosio et al () and Aguirrezábal et al () revealed that oil content is affected by the amount of solar radiation intercepted by a cultivar especially during anthesis. Agronomic techniques such as foliar application of molybdenum at 125 g Mo ha −1 at V‐4 (4 leaves stage) and varying nutritional area (spacing) have also been reported to result in relative increase in oil content of sunflower by Skarpa et al () and Ahmad et al (), respectively. These findings will be factored into future studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although, we did not quantify the amount of solar radiation intercepted by the test varieties in this study, Dosio et al () and Aguirrezábal et al () revealed that oil content is affected by the amount of solar radiation intercepted by a cultivar especially during anthesis. Agronomic techniques such as foliar application of molybdenum at 125 g Mo ha −1 at V‐4 (4 leaves stage) and varying nutritional area (spacing) have also been reported to result in relative increase in oil content of sunflower by Skarpa et al () and Ahmad et al (), respectively. These findings will be factored into future studies.…”
Section: Discussionmentioning
confidence: 98%
“…The genetic basis of high morphological variability resulting in branching of sunflower is not fully understood (Sandu et al , ). Seed oil content which is an important selection criterion in the improvement of sunflower varies among cultivars (Lopez et al , ; Leon et al , ; Chigeza et al , ) and is affected by the amount of solar radiation intercepted by the cultivar (Dosio et al , ; Aguirrezábal et al , ), temperature (Rondanini et al , ; Khan et al ., ), sowing date, genotype, and their interactions (de la Vega & Hall, 2002 a , b ; Aslam et al , ; Lawal et al , ), plant density (Barros et al , ; Zarea et al , ) and foliar application of molybdenum at V‐4, four developed leaves stage (Skarpa et al , ). Oil content in sunflower is a function of the maternal plant genotype and not by kernel genotype (Thompson et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that Se can play diverse beneficial effects at low concentrations including growth-promoting activities of higher plants [ 38 ]. Molybdenum, as one of the micronutrients that plants need in very small amounts for normal growth, has also been proved to improve the growth parameters in different plants, such as Helianthus annuus L. [ 39 , 40 ], Brassica napus [ 41 ], and other plants. The stimulating effect of Mo on plant biomass might be due to its role as a cofactor for enzymes involved in nitrate metabolism (such as nitrate reductase and glutamine synthetase) and synthesis of amino acids and indole acetic acid [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foliar fertilization is an increasingly popular practice with particular importance for the production of high value crops (Fernández and Brown, 2013; Fernández et al, 2013) such as sunflowers with many examples of positive responses to foliar application of micronutrients, including zinc (Zn), iron (Fe), boron (B), manganese (Mn), and molybdenum (Mo), on the seed yield and seed quality of sunflower (Jabeen et al, 2013; Skarpa, 2013; Skarpa et al, 2013; Tohidi-Moghadam, 2013; Yang et al, 2013; Tahir et al, 2014). Foliar fertilization has particular value in overcoming nutrient deficit resulting from stress conditions, such as salinity and drought, which often compromise root growth and decrease root absorption capacity (Kannan, 2010).…”
Section: Introductionmentioning
confidence: 99%